Validity and reliability of Gripwise digital dynamometer in the assessment of handgrip strength in older adults - Benatti de Oliveira, Gabriela; Vilar Fernandes, Lara; Amaral, Teresa F.; Vasques, Ana Carolina Junqueira; Pires Corona, Ligiana (Frontiers in Aging, 2025)
IntroductionWith the advancement of studies on the importance of sarcopenia in the aging process, new technologies have been developed to assess muscle mass and function. However, most research on portable devices has not considered a wide range of ages and clinical conditions. This study aimed to evaluate the reliability of the Gripwise digital dynamometer in measuring handgrip strength in older Brazilian adults, comparing its performance with the widely used Saehan device.MethodsA cross-sectional study was conducted with 149 participants (32 men and 117 women), with an average age of 69.5 years. Handgrip strength was measured using both the Gripwise and Saehan dynamometers. Reliability was assessed using the intraclass correlation coefficient (ICC). Analyses considered three handgrip strength measurements from both devices, as well as the highest value obtained. The classification of dynapenia (low muscle strength) was compared using different cutoff points proposed by Villain et al. (2023), Spexoto et al. (2022), and Cruz-Jentoft et al. (2019).ResultsBoth dynamometers demonstrated excellent reliability, with ICC values above 0.90. However, significant differences in mean handgrip strength values were observed between the devices (approximately 3.5–four kgf). These variations impacted the classification of dynapenia, with the Gripwise identifying more cases of low muscle strength compared to Saehan.ConclusionThe lower values reported by the Gripwise may impact clinical decision-making in two ways. On one hand, lower values may lead to earlier detection of muscle weakness, allowing for quicker intervention in individuals with strength below typical thresholds. However, this could also result in an overestimation of the prevalence of dynapenia if the values do not accurately reflect true muscle strength, which could lead to unnecessary interventions. Therefore, it is crucial to consider the need for adjustments in the cutoff points when using Gripwise. These findings highlight the need to revise cutoff points for dynapenia classification, considering device variations and model differences in older age groups.